Employee Based Brand Equity: Building Brand Value for Employees through Internal Branding - Ezgi Erkmen (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
The purpose of this study is to examine the role of internal branding in explaining employees brand equity in service industry. A conceptual model, which incorporates the internal branding mechanisms, namely the human resources, leadership, and internal communication, is proposed to understand their effect on employee based brand equity. A quantitative research methodology, using structural equation modeling, was adopted to understand the role of internal branding in creating brand equity for employees. Data were collected from the customer contact employees in hotel and restaurant industry. The findings supported the sequential link for: internal branding – brand awareness – brand image and perceived quality – brand commitment. Even only internal communication and leadership were found to significantly affect brand awareness; this brand knowledge was then positively influenced the brand image and perceived brand quality of employees. Moreover, the results found that as employees have a more positive perception of brand image and quality, they are more likely to be committed to the company brand. Therefore, this study confirmed the importance of internal branding to increase employee brand equity, which in turn, translates into a strong brand for customers. In addition, this research is one of the limited studies adopting an employee perspective for brand equity as well as studying the role of internal branding mechanisms in building that brand equity.